2003
DOI: 10.1046/j.1467-7652.2003.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved forage digestibility of tall fescue (Festuca arundinacea) by transgenic down‐regulation of cinnamyl alcohol dehydrogenase

Abstract: SummaryLignification of cell walls during plant development has been identified as the major factor limiting forage digestibility and concomitantly animal productivity. cDNA sequences encoding a key lignin biosynthetic enzyme, cinnamyl alcohol dehydrogenase (CAD), were cloned from the widely grown monocotyledonous forage species tall fescue ( Festuca arundinacea Schreb.). Recombinant tall fescue CAD expressed in E. coli exhibited the highest V max / K m values when coniferaldehyde and sinapaldehyde were used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
2
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 61 publications
(116 reference statements)
3
83
2
4
Order By: Relevance
“…Improvements in alfalfa forage digestibility by downregulation of the ''late'' pathway enzymes COMT and CAD (28)(29)(30) are considerably less than achieved here with C3H or C4H down-regulation. For development of agronomically viable lines, it may be necessary to further fine-tune the level of C3H or C4H expression to eliminate the possibility of reduced growth.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Improvements in alfalfa forage digestibility by downregulation of the ''late'' pathway enzymes COMT and CAD (28)(29)(30) are considerably less than achieved here with C3H or C4H down-regulation. For development of agronomically viable lines, it may be necessary to further fine-tune the level of C3H or C4H expression to eliminate the possibility of reduced growth.…”
Section: Discussioncontrasting
confidence: 61%
“…1 have been identified, and many of the enzymatic steps have been down-regulated in transgenic plants. The results of these studies (24)(25)(26)(27)(28)(29)(30) have generally confirmed the pathway in Fig. 1 and supported increasing S͞G ratio as a means of improving paper pulping in trees.…”
supporting
confidence: 72%
“…but not H units, and decreased S/G ratio (Chen et al, 2003). The in vitro dry matter digestibility is increased by 7.2-9.5% compared to controls (Chen et al, 2003).…”
Section: Cinnamyl Alcohol Dehydrogenasementioning
confidence: 80%
“…Coniferaldehyde and sinapaldehyde are preferred substrates for CAD in tall fescue (Chen et al, 2003).…”
Section: Cinnamyl Alcohol Dehydrogenase (Cad)mentioning
confidence: 99%
See 1 more Smart Citation